SIZE OF PUBLIC SECTOR IN MALAYSIA: PREMIERSHIP OF PRIME MINISTERS (Journal of Business Management and Accounting, 2022)
This study aims to evaluate the size of the public sector during the premiership of three former prime ministers of Malaysia. The size of the public sector in Malaysia was measured based on total expenditure for the period 1982 - 2015. A comparison of public sector size based on the percentage of total public sector expenditure to GDP suggests that the size of the public sector was bigger during the early years of Tun Dr. Mahathir’s premiership; the percentage remained at a low level from 1994 onwards and continued during the tenure of his successors.  The trend in the size of the public sector of the three prime ministers ranges from 15% to 30%, which means that the Malaysian government's sizing practices are consistent with other countries. Taking into account the government’s operating expenditure to total expenditure, the percentage of operating expenditure increased during the premiership of Dato’ Sri Najib. The government policy in the days of Dato’ Sri Najib focused on implementing government reform programs and increasing employment, which could have led to higher operating expenditure compared to development expenditure.  Based on trends in government spending, the size of the government can be related to political or policy changes and economic conditions during the said prime ministers’ tenure.